INSENTIF PAJAK, BANTUAN STIMULUS PEMERINTAH PADA KINERJA USAHA MIKRO KECIL MENENGAH DI KABUPATEN BOYOLALI - Dwi Septi Lestari; Siti Nurlaela; Riana R Dewi (UNIVED Press, 2021)
The world was in an uproar with the outbreak of a new virus in early 2020, namely the corona virus (SARS-CoV). It is called Corona virus during the 2019 period (COVID-19). Covid-19 is a contagious disease and this transmission causes public concern, thus affecting their social and economic life. Government policies appeal to the public to social distancing and isolate themselves at home. The small, micro and medium enterprises (UKM) sector has an important role in maintaining local and government economic activities. The objective of this research is to determine the effect of tax incentives and government stimulus assistance on the performance of UMKM in Boyolali Regency. The population in the research is all people in Boyolali who have micro, small and medium enterprises (UMKM) with the random sampling method and the number of samples is 93. The research used primary data. The method to determine the effect between the independent variable and the dependent variable is the research instrument test, classical assumption test, and multiple regression analysis tests using SPSS 23 version. Based on the research, the results show that tax incentives and government stimulus assistance affect the performance of UMKM in the Boyolali regency.